2003
DOI: 10.1061/(asce)0733-9372(2003)129:12(1137)
|View full text |Cite
|
Sign up to set email alerts
|

Iodide-Enhanced Electrokinetic Remediation of Mercury-Contaminated Soils

Abstract: This study investigates using an iodide-enhanced solution at the cathode during electrokinetic treatment to optimize the removal of mercury from soils. The experimental program consisted of testing two types of clayey soils, kaolin, and glacial till, that were initially spiked with 500 mg/kg of Hg͑II͒. Experiments were conducted on each soil type at two voltage gradients ͑1.0 or 1.5 VDC/cm͒ to evaluate the effect of the voltage gradient when employing a 0.1 M KI solution. Additional experiments were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Electrokinetic remediation of heavy metals in soils has been investigated at the University of Illinois at Chicago [2][3][4][5][6]. These studies demonstrated that in low buffering soils such as kaolin with water as the electrolyte solution, targeted metal cations such as nickel and cadmium migrate toward the cathode and are immobilized before they reach the cathode.…”
Section: Introductionmentioning
confidence: 98%
“…Electrokinetic remediation of heavy metals in soils has been investigated at the University of Illinois at Chicago [2][3][4][5][6]. These studies demonstrated that in low buffering soils such as kaolin with water as the electrolyte solution, targeted metal cations such as nickel and cadmium migrate toward the cathode and are immobilized before they reach the cathode.…”
Section: Introductionmentioning
confidence: 98%
“…As Hg also forms soluble species according to the following reactions (Cox et al 1996;Reddy et al 2003b):…”
Section: Chemistry Of Mercury and Implications For Soil-sediment Remementioning
confidence: 99%
“…As the transformation of most heavy metals is pH dependent, keeping the soil at low pH appears to be a plausible solution. Techniques being investigated include simultaneous injection of enhancement agents, such as purging solutions (synthetic or natural), chelating agents, and complexing agents including sulfuric acid, citric acid (Eykholt and Daniel 1994;Gu et al 2009b), EDTA (Yeung et al 1996), iodine/iodide lixiviant (Cox et al 1996;Reddy et al 2003), humic acid, sodium acetate solution, nitric acid, to transform the contaminants to their mobile phases so that they can be effectively removed; acetic acid depolarization of the cathode reaction, and use of ion-selective membrane to veil hydroxide ions back-transport at the cathode (Rødsand et al 1995); and conditioning of electrodes and reservoir solutions to specific pH to eliminate the adverse impacts of electrode reactions (Lee and Yang 2000). More research on these physicochemical soil-contaminant interactions is certainly needed to develop better enhancement techniques for electrokinetic extraction (Yeung 2009b).…”
Section: Enhancement Of Electrokinetic Extractionmentioning
confidence: 99%